Wide Band frequency fixed current source for BIT and BIA - Ar-Rawi, A.H. (2009)
High frequency bioelectrical impedance analysis devices are mostly used in Bioimpedance tomography and blood analysis. Nowadays 50 - 100 KHz bioelectrical impedance devices are commonly used for body composition analysis. AD8130 or AD 8129 deferential op-amp is used in this paper. These two op-amps offer high output impedances at low frequencies because of the amplifiers' good low-frequency CMRR (common-mode-rejection ratios). At higher frequencies, decreasing CMRR, inherent output capacitances, and slew-rate limitations prevent realization of high-quality current sources. 170 mV sine wave signal is used as input voltage considering the current should be no more than 1 mA. Four frequencies of 100 KHz, 1 MHz, 2 MHz and 3.2 MHz are applied to the circuit and by changing the load resistor, the current is measured. The result shows the current stable during the load resistor changing.